Positional Cervical Dystonia - Belenky, Vadim (Research Highlights in Disease and Health Research Vol. 6, 2023)
Cervical dystonia, or spasmodic torticollis, refers to involuntary dystonic movements of the head that may be associated with certain body and neck positions. Those positions could either improve or enhance hyperkinesis. The pathophysiology of dystonia is not fully examined. Thus, researchers are confused by the phenomena of low penetrance of inherited dystonia. In the same family, the phenotype among the carriers of dystonia mutation varies from absolute norm in most of them, to profound generalized suffering in minority, meanwhile triggering factors of the penetrance of dystonia remain unknown. We report a case of torticollis, that was unusual in the sense, that it occurred only when the patient was lying on one side, and completely disappeared in any other situations. The cause of the cervical dystonia in this patient was unknown, and the positional nature of the movements was unusual.